SOCIAL EVILS IN MEDIA: CHALLENGES AND SOLUTIONS IN 21ST CENTURY - Shahid, Anam; Sumbul, Maria (PEOPLE: International Journal of Social Sciences, 2017)
echnology and social media has become a vital part of daily lives of people, especially children. There are advantages of using technology and being active on social media but there are equal disadvantages and risks that come along with excessive use of electronic devices. As per American Academy of Pediatricians children are spending 7 hours a day on media such as computers, phones, I-pads, television and other electronic devises. A child as young as age 2 starts using mobile phone to view rhymes and videos on you tube which brings many risks to their health and wellbeing. This paper reviews the literature and discusses the problems caused by social media, technology such as obesity, aggressive behavior, negative effects on mental health, cyber bullying, texting/sexting and contact to problematic and illegal content etc. in children from age 2 till 18. The paper highlights the ratio of UAE parents, who are aware of social evils and take measures to protect their children. Also, the study attempts to provide solutions and guidelines from pediatricians that would be helpful for parents and individuals, in addressing the difficulties instigated by electronic devices and social media in addition to molding their children as healthier citizens. We hope that this paper will make relevant institutions provide more educational platforms to parents in order to spread awareness about the impact of media on children along with appropriate measures that can be taken to deal with it.